1992
DOI: 10.2307/3857568
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios in Business Ethics Research: Review, Critical Assessment, and Recommendations

Abstract: A growing number of researchers in the business ethics field have used scenarios as a data gathering technique in their empirical investigations of ethical issues. This paper offers a review and critique of 26 studies that have utilized scenarios to elicit inferences of ethical reasoning, decision making, and/or intended behavior from managerial or student populations. The use of a theoretical foundation, the development of hypotheses, various characteristics germane to the use of scenarios, population and sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
142
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(153 citation statements)
references
References 42 publications
4
142
1
3
Order By: Relevance
“…Randall and Gibson (1990) also found that the middle bands (21%-50%) were the most common, which is consistent with the accounting ethics mail surveys. Weber (1992) found response rates for random sampling ranged from 21% to 76%, which again is broadly in line with the accounting ethics literature (we found 10% to 70%). Unfortunately, Weber does not give the mean figure, which would provide a more meaningful comparison.…”
Section: Sampling and Response Ratessupporting
confidence: 77%
See 4 more Smart Citations
“…Randall and Gibson (1990) also found that the middle bands (21%-50%) were the most common, which is consistent with the accounting ethics mail surveys. Weber (1992) found response rates for random sampling ranged from 21% to 76%, which again is broadly in line with the accounting ethics literature (we found 10% to 70%). Unfortunately, Weber does not give the mean figure, which would provide a more meaningful comparison.…”
Section: Sampling and Response Ratessupporting
confidence: 77%
“…It is even more contentious to suggest that the results of surveys using students' responses to questionnaires involving business scenarios are reliable as proxies for practitioners, as it may be difficult for students to respond adequately to situations they know little about in practical terms (Weber, 1992). However, this will, to a large degree, depend on the student group as some groups (for example postgraduate) may contain individuals who have relevant experience.…”
Section: Sampling and Response Ratesmentioning
confidence: 99%
See 3 more Smart Citations